Factors that Influence Parents’ Meta-Emotion Approaches: Implications for Families - Mechler, Hannah Mills; McCarroll, Elizabeth (International Journal of Emerging Trends in Social Sciences, 2017)
This quantitative study investigated the concept of meta-emotion by examining factors that were associated with specific types of meta-emotion approaches parents used. The main variables included parental stress, outside support, education levels. Other variables considered were number of children in the family, age of children, and children’s gender. The concept of meta-emotion as well as the inclusion of these variables were important to investigate to further understand the factors that influenced parents’ thoughts and reactions to their children’s emotions and emotional responses. It was determined that 143 participants were needed. These participants were gathered by emails sent to students and faculty at Texas Woman’s University. Participants were also gathered by dispersing flyers advertising the study in the Dallas-Fort Worth, Texas metroplex. Individuals who agreed to participate gave consent and then completed the anonymous online questionnaires through PsychData. Results yielded that parental stress was the only significant predictor of meta-emotion approaches.